2012
DOI: 10.1038/tp.2012.97
|View full text |Cite
|
Sign up to set email alerts
|

Neurite outgrowth mediated by the heat shock protein Hsp90α: a novel target for the antipsychotic drug aripiprazole

Abstract: Aripiprazole is an atypical antipsychotic drug approved for the treatment of psychiatric disorders such as schizophrenia, bipolar disorder, major depressive disorder and autism. The drug shows partial agonistic activity at dopamine D2 receptors and 5-hydroxytryptamine (5-HT) 5-HT1A receptors, and antagonistic activity at 5-HT2A receptors. However, the precise mechanistic pathways remain unclear. In this study, we examined the effects of aripiprazole on neurite outgrowth. Aripiprazole significantly potentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 61 publications
0
21
1
Order By: Relevance
“…Our previous studies with two different patients cohorts have showed decreased mossy fiber sprouting in MTLE patients with psychosis, 6,7 which might be related to decreased synaptic markers found in schizophrenia, 36 as well as to the decreased HSP90 expression we reported here. Of note, despite the HSP90 augmentation in PC12 cell culture shown with aripiprazole, 35 we found decreased HSP90 expression in the granular layer and subiculum of MTLE+P patients taking haloperidol. Possible explanations include a diverse action of haloperidol on HSP90 levels or, in case of similar effect, different outcomes would be expected when comparing in vitro and in vivo situations due to significant increase of system complexity.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Our previous studies with two different patients cohorts have showed decreased mossy fiber sprouting in MTLE patients with psychosis, 6,7 which might be related to decreased synaptic markers found in schizophrenia, 36 as well as to the decreased HSP90 expression we reported here. Of note, despite the HSP90 augmentation in PC12 cell culture shown with aripiprazole, 35 we found decreased HSP90 expression in the granular layer and subiculum of MTLE+P patients taking haloperidol. Possible explanations include a diverse action of haloperidol on HSP90 levels or, in case of similar effect, different outcomes would be expected when comparing in vitro and in vivo situations due to significant increase of system complexity.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition to the role in prevention of microtubule disassembly, HSP90, unlike other HSPs, may initiate neurite outgrowth, . In fact, a recent study by Ishima et al . suggests that treatment with the atypical antipsychotic drug aripiprazole may potentiate nerve growth factor (NGF)‐induced neurite outgrowth through enhanced HSP90 expression, although it is unclear how HSP90 contributes to its therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D2R partial agonist aripiprazole is used to treat psychiatric disorders including schizophrenia, major depression, bipolar, and autism. Cell culture studies show that aripiprazole potentiates nerve growth factor‐induced neurite outgrowth in PC12 cells . Brexpiprazole has a similar pharmacological profile to aripiprazole and also significantly potentiated nerve growth factor–induced neurite outgrowth in PC12 cells in a concentration‐dependent manner .…”
Section: The Effects Of Antipsychotic Drugs On Neuritesmentioning
confidence: 93%
“…NGF binds to its recep-tor and activates the ERK/CREB pathway, leading to the downstream c-FOS, EGR1, c-JUN, FOSB, and JUNB expression to promote neurite outgrowth in PC12, and treatment with the ERK-specific inhibitor of U0126 inhibits NGF-induced and aripiprazole-enhanced neurite outgrowth (Harada et al 2001;Pellegrino and Stork 2006;Eriksson et al 2007;Ravni et al 2008;Chung et al 2010;Mullenbrock et al 2011;Ishima et al 2012;Kudo et al 2013). Similarly, artemisinin and its derivatives induce neurite outgrowth of PC12 cells in an ERK/CREB dependent manner (Sarina et al 2013).…”
Section: Discussionmentioning
confidence: 99%